Glaucoma in aphakia and pseudophakia in the Chennai Glaucoma Study. Issue 6 (27th May 2005) - Arvind, H; George, R; Raju, P; Ramesh, S V; Baskaran, M; Paul, P G; McCarty, C; Vijaya, L
Abstract : Aim: To determine the prevalence of glaucoma among aphakes and pseudophakes in a rural population of southern India. Methods: 3924 subjects aged 40 years or above underwent complete ophthalmic examination. Glaucoma in aphakia/pseudophakia was diagnosed using International Society of Geographical and Epidemiological Ophthalmology criteria in aphakic/pseudophakic people. Results: 54 subjects (37 aphakes, 17 pseudophakes) (1.38% of 3924 subjects, 11.2% of 482 aphakes/pseudophakes) had glaucoma in aphakia/pseudophakia. Aphakia, age, intraocular pressure (IOP), pseudoexfoliation, and peripheral anterior synechiae greater than or equal to 180 degrees of the angle were risk factors for glaucoma on univariate analysis. On multivariate analysis, IOP and aphakia were independent risk factors for glaucoma. 39 people (72.22%) with glaucoma had normal IOP at presentation. None of the people with glaucoma were aware of the disease. Blindness in one or both eyes was seen in 12 subjects (10 unilateral and two bilateral)—that is, 22.22% of people with glaucoma in aphakia/pseudophakia. Conclusions: Glaucoma is an important cause of ocular morbidity among aphakes and pseudophakes in this rural population of south India. This glaucoma, responsible for unilateral or bilateral blindness in 22.2% of those affected, was entirely undetected in this study population.